Qualitative assay of C-reactive proteins in acute coronary syndromes - Appajigol, Jayaprakash; Srinivasmurthy, A G (International Multidisciplinary Research Journal, 2013)
Introduction: Acute coronary syndromes (ACS) are the major causes of mortality in coronary care units. Inflammation plays an important role in ACS. C-reactive protein (CRP) is one of the inflammatory markers, which plays a key role in the pathogenesis. This study aimed at assessing C-reactive protein levels in acute coronary syndromes, and determining its significance in prognosis. Methods: Fifty patients admitted with the diagnosis of ACS were included in the study. Qualitative C - reactive protein assay was done at the time of admission. Patients were followed up for the complications till discharge. Results: Age group between 41 to 70 years constituted 40 (80%) patients. Out of 50 patients with acute coronary syndromes 36 patients had elevated CRP. Thirty patients (83.33%) of them met with complications. Of the 14 patients with low CRP only two (14.28%) patients met with the complications. Conclusions: Qualitative plasma CRP estimation gives valuable prognostic information in acute coronary syndromes.